Proceedings 2006 IEEE International Conference on Robotics and Automation, 2006. ICRA 2006.
DOI: 10.1109/robot.2006.1642248
|View full text |Cite
|
Sign up to set email alerts
|

Towards particle filter SLAM with three dimensional evidence grids in a flooded subterranean environment

Abstract: This paper describes the application of a RaoBlackwellized Particle Filter to the problem of simultaneous localization and mapping onboard a hovering autonomous underwater vehicle. This vehicle, called DEPTHX, will be equipped with a large array of pencil-beam sonars for mapping, and will autonomously explore a system of flooded tunnels associated with the Zacatón sinkhole in Tamaulipas, Mexico. Due to the threedimensional nature of the tunnels, we describe an extension of traditional two dimensional evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…(Williams et al, 2000), (Hernàndez et al, 2009), and (Fairfield et al, 2006)). The work of Thurn (Thrun et al, 2005) includes a good survey of the core techniques capable of fusing data from multiple sensors to create maps.…”
Section: Mapping Via Underwater Robot Systemsmentioning
confidence: 99%
“…(Williams et al, 2000), (Hernàndez et al, 2009), and (Fairfield et al, 2006)). The work of Thurn (Thrun et al, 2005) includes a good survey of the core techniques capable of fusing data from multiple sensors to create maps.…”
Section: Mapping Via Underwater Robot Systemsmentioning
confidence: 99%
“…In May 2005, the DEPTHX team lowered a 32-sonar probe, called the DropSonde, into Zacatón to a depth of 200m (Figure 1) (Fairfield et al 2006). A similar probe, called the Digital Wall Mapper (DWM) was used in 1998-1999 to map several kilometers of the Wakulla Springs cave system in Florida (Stone et al 2000).…”
Section: Wakatónmentioning
confidence: 99%
“…In (Fairfield et al 2006), we demonstrated SLAM in a constrained scenario with real-world sonar data from Zacatón. In this work, we show that will be able to perform 3D SLAM in real-time on the DEPTHX vehicle.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we focus on the 3D map representation, see (Fairfield et al 2006;2007) for a more complete description of our simultaneous localization and mapping (SLAM) approach.…”
Section: Analysis and Processing Of Spatial Datamentioning
confidence: 99%
“…For reasonable map sizes and resolutions, the memory requirements quickly become intractable, especially considering that our particle filter SLAM approach requires multiple maps to represent different possible vehicle trajectories. To circumvent this storage and processing problem, we use the Deferred Reference Counting Octree data structure described by Fairfield et al (2007). This data structure exploits shared regions between particle maps and efficiently represents sparse volumes, yielding a significant performance boost that allows us to represent maps that would not even fit into memory as a uniform array.…”
Section: Analysis and Processing Of Spatial Datamentioning
confidence: 99%